KEPEMIMPINAN KEPALA SEKOLAH MENUJU PEMBELAJARAN ABAD 21 DI SD NEGERI 161 PEKANBARU - Ema Yurista Diani; Dea Mustika (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2024)
The aim of this research is to describe the principal's leadership towards 21st century learning and what the obstacles are at SD Negeri 161 Pekanbaru. The method used in this research is Qualitative Descriptive with data collection instruments of observation, interviews and documentation. Primary data sources are school principals and teachers. Secondary data sources are journals, books and supporting documentation such as photos. Data validity uses source triangulation, technical triangulation, and time triangulation. With data analysis techniques, data reduction, data presentation and drawing conclusions. The results of the principal's leadership towards 21st century learning at SDN 161 Pekanbaru were obtained, namely, the principal implemented, a) Implemented a deliberative and democratic approach in the meeting decision-making process b) Utilized social media such as WhatsApp, Instagram, Facebook, email and YouTube c) Supported developing student and teacher creativity through various activities d) Routinely evaluating the performance of teachers and staff through supervision e) Holding regular training programs to improve teacher performance and human resource development.